2019
DOI: 10.1101/838540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytochromecas a facultative enzyme – lipoperoxidase and it’s inhibition by antioxidants

Abstract: Many researchers consider a key role in initiation of apoptosis along the mitochondrial pathway to be enhanced by cytochrome c, one of the components of the mitochondrial respiratory chain, which acquires peroxidase activity by forming a complex with phospholipids. Mitochondrial membranes are destroyed affected by the peroxidase reaction catalyzed by this supramolecular nanoparticle, resulting in the release of various proapoptotic factors into the cellular cytoplasm, ultimately leading to the development of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, despite its structure, C-525 is quite often used as a chemiluminescence activator; e.g., when detecting lipid hydroperoxides in the lipid substrate– Fe 2+ system [ 16 ]. Experiments in a similar system based on C-334 showed that the chemiluminescence of the system containing cytochrome c complexed with cardiolipin is due to the lipoperoxidase and quasi-lipoxygenase activity of this nanoparticle, but not to the activity of non-heme iron via the Fenton reaction [ 81 ].…”
Section: Search For Physical Enhancers Of the Chemiluminescence Accom...mentioning
confidence: 99%
“…However, despite its structure, C-525 is quite often used as a chemiluminescence activator; e.g., when detecting lipid hydroperoxides in the lipid substrate– Fe 2+ system [ 16 ]. Experiments in a similar system based on C-334 showed that the chemiluminescence of the system containing cytochrome c complexed with cardiolipin is due to the lipoperoxidase and quasi-lipoxygenase activity of this nanoparticle, but not to the activity of non-heme iron via the Fenton reaction [ 81 ].…”
Section: Search For Physical Enhancers Of the Chemiluminescence Accom...mentioning
confidence: 99%
“…Models based on biological molecules isolated from living organisms. Examples include cytochrome c and cardiolipin isolated from animals [ 20 ] and Escherichia coli DNA [ 1 ];…”
Section: Biological Model Systems In the Study Of Free Radical Reactionsmentioning
confidence: 99%